(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
A person’s body, intellect, and character are all shaped and reinforced throughout the course ofeducation. It’s a way to unite the mind, heart, and body of a person so that they can discover their ownunique set of strengths and abilities. Since independence, higher education in India has grownsignificantly, yet it is not available to everyone. At around 9 percent each year, India is currently one of theworld’s fastest-growing economies. As of this writing, many people are still illiterate and many children arenot receiving even elementary education. While many individuals have been left out of this country’sgrowth, they have also been unable to completely benefit from it. Globally, states’ educationalinstitutions are now understood to be a key factor in their economic prosperity. Our strength lies in oureducation system. A highly educated populace is a given in every advanced economy. The Indian highereducation system has 51,649 institutions, making it the third biggest in the world. The present paper aimto identify issues and challenges in the fields of Higher Education in India.